THE IMPLICATION OF INFORMATION SYSTEM (IS) SUCCESS MODEL ON CLOUD-BASED M-RETAIL ADOPTION INTENTION AMONG TEXTILE CYBERPRENEURS - Wan Safra Diyana Wan Abdul Ghani; Nik Zulkarnaen Khidzir; Mohammad Ismail (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2021)
Nowadays, the uses of mobile phones in conducting business operations among entrepreneurs are not unusual. Varieties of apps have been developed in order to accommodate the needs of business owners in ensuring smooth business transactions regardless of location and time. One of the apps that could help entrepreneurs to perform selling and buying activities is the cloud-based mretail application (CBMA). In Malaysia, Malaysian entrepreneurs such as textile cybrepreneurs are known to utilise this app but academic studies on this context were rarely done. From previous studies, quality traits of a system have been found to play significant roles in attracting users to utilise the system. Therefore, this study focuses on examining the influences of CBMA qualities towards textile cyberpreneurs’ intention to adopt CBMA based on the Information System (IS) Success Model. 348 textile cyberpreneurs have participated in this study and the results have shown system quality, information quality and service quality have significant positive influences on CBMA adoption intention. Practical implications and future recommendations are also introduced for further reading comprehension.